2014
DOI: 10.2478/s13382-014-0240-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between subclinical hypothyroidism and metabolic syndrome components among workers

Abstract: Objectives: Both hyperthyroidism and overt hypothyroidism are associated with increased prevalence of metabolic syndrome and its components, while data on subclinical hypothyroidism is currently limited especially in working populations. The aim of this study was to examine the association between subclinical hypothyroidism and metabolic syndrome components in workers; and to evaluate whether there are differences by sex and occupation. Material and Methods: A total of 1150 university employees (male -792, fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
11
2
Order By: Relevance
“…22 This study shows the significant difference in lipid parameters between cases and controls group. Elevated serum concentrations of TC, TG and LDL-cholesterol in SCH patients were supported by MJ Cheserek et al study who reported that subclinical hypothyroidism was associated with metabolic syndrome components in males, not in females 23 while the higher concentration of HDL-cholesterol in the control group is supported by Erdum YT et al 24 Clinical and epidemiological studies have found that for the effectiveness of lowering the lipid concentration the ratio between LDL-cholesterol to HDL-cholesterol is an excellent marker. It was concluded that this LDL-cholesterol/HDL-cholesterol ratio describe the two-way route of cholesterol entering and exiting the arterial intima.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…22 This study shows the significant difference in lipid parameters between cases and controls group. Elevated serum concentrations of TC, TG and LDL-cholesterol in SCH patients were supported by MJ Cheserek et al study who reported that subclinical hypothyroidism was associated with metabolic syndrome components in males, not in females 23 while the higher concentration of HDL-cholesterol in the control group is supported by Erdum YT et al 24 Clinical and epidemiological studies have found that for the effectiveness of lowering the lipid concentration the ratio between LDL-cholesterol to HDL-cholesterol is an excellent marker. It was concluded that this LDL-cholesterol/HDL-cholesterol ratio describe the two-way route of cholesterol entering and exiting the arterial intima.…”
Section: Methodssupporting
confidence: 55%
“…18 Significant differences in this cross-sectional study, between SCH male patients and control group, supported the hypothesis that SCH patients are associated with metabolic syndrome components in males. 19 Madathil A et al observed that fatigue and another impaired functional status was associated with SCH males. 20 There was increased BMI in SCH males compared to control group.…”
Section: Methodsmentioning
confidence: 99%
“…The study participants were university employees on routine annual clinical examination at the Jiangnan University hospital. In our previous work ( 24 ), we found high prevalence of metabolic syndrome and its components among male workers compared to females (n=2428) that was attributed to occupation type and SCH ( 25 ). In the present study, we further examined whether there was increased oxidative stress in randomly selected males (35–59 years) with SCH (n=467) compared with individuals with normal thyroid function (n=190).…”
Section: Methodsmentioning
confidence: 77%
“…Hadaegh et al [16] found that female gender had lower risk for incident of MetS than male [HR: 0.58 (0.47-0.70)]. Also, Cheserek et al [22] showed that subclinical hypothyroidism was associated with metabolic syndrome components in males but not in females.…”
Section: Prace Oryginalnementioning
confidence: 98%